A benchmark study of numerical schemes for one‐dimensional arterial blood flow modelling. (3rd July 2015) - Boileau, Etienne; Nithiarasu, Perumal; Blanco, Pablo J.; Müller, Lucas O.; Fossan, Fredrik Eikeland; Hellevik, Leif Rune; Donders, Wouter P.; Huberts, Wouter; Willemet, Marie; Alastruey, Jordi
Summary Hæmodynamical simulations using one‐dimensional (1D) computational models exhibit many of the features of the systemic circulation under normal and diseased conditions. Recent interest in verifying 1D numerical schemes has led to the development of alternative experimental setups and the use of three‐dimensional numerical models to acquire data not easily measured in vivo. In most studies to date, only one particular 1D scheme is tested. In this paper, we present a systematic comparison of six commonly used numerical schemes for 1D blood flow modelling: discontinuous Galerkin, locally conservative Galerkin, Galerkin least‐squares finite element method, finite volume method, finite difference MacCormack method and a simplified trapezium rule method. Comparisons are made in a series of six benchmark test cases with an increasing degree of complexity. The accuracy of the numerical schemes is assessed by comparison with theoretical results, three‐dimensional numerical data in compatible domains with distensible walls or experimental data in a network of silicone tubes. Results show a good agreement among all numerical schemes and their ability to capture the main features of pressure, flow and area waveforms in large arteries. All the information used in this study, including the input data for all benchmark cases, experimental data where available and numerical solutions for each scheme, is made publicly available online, providing a comprehensive reference data set to support the development of 1D models and numerical schemes. Copyright © 2015 John Wiley & Sons, Ltd.